2007
DOI: 10.1007/s11608-007-0108-2
|View full text |Cite
|
Sign up to set email alerts
|

Propriétés pharmacologiques de l’oxybutynine sur la fonction vésicale chez la souris

Abstract: Les antagonistes muscariniques, comme l'oxybutynine, sont le principal traitement pharmacologique actuel pour l'incontinence urinaire par urgenturie. L'objectif de cette étude a été d'évaluer l'activité pharmacologique de l'oxybutynine sur la fonction vésicale chez la souris. Pour cela, nous avons développé des nouveaux modèles expérimentaux nous permettant d'étudier, in vitro, sa puissance antagoniste sur la vessie isolée et in vivo, son urosélectivité au regard des effets sur les glandes salivaires ainsi que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…9 An experimental work on mice as models showed that, as in rats and humans, oxybutynin efficiently acts on the efferent pathway of the urinary reflex. 10 Although being efficacious as a drug, oxybutynin has side effects so bothersome that some patients prefer to discontinue treatment and to endure the drawbacks of overactive bladder. 8 Acomplete list of oxybutynin unwanted effects has been produced by the Drugs.com website, 11 those requiring the most attention being eye pain, skin rash, dizziness and irregular heartbeat.…”
Section: Introductionmentioning
confidence: 99%
“…9 An experimental work on mice as models showed that, as in rats and humans, oxybutynin efficiently acts on the efferent pathway of the urinary reflex. 10 Although being efficacious as a drug, oxybutynin has side effects so bothersome that some patients prefer to discontinue treatment and to endure the drawbacks of overactive bladder. 8 Acomplete list of oxybutynin unwanted effects has been produced by the Drugs.com website, 11 those requiring the most attention being eye pain, skin rash, dizziness and irregular heartbeat.…”
Section: Introductionmentioning
confidence: 99%